Pharmacogenomics in Intracranial Atherosclerotic Disease: CYP2C19 Loss-Of-Function is Associated with Increased Risk of First-time Ischemic Stroke. (16th November 2020) - Patel, Pious D; Vimalathas, Praveen; Niu, Xinnan; Shannon, Chevis; Peterson, Josh; Fusco, Matthew; Chitale, Rohan V
Abstract: INTRODUCTION: Intracranial atherosclerotic disease (ICAD) is responsible for 8–10% of acute ischemic stroke (AIS). Angioplasty and stenting have unproven efficacy for ICAD. Antiplatelet medical therapy is the mainstay, but resistance is highly prevalent. CYP2C19 gene loss-of-function (up to 45% of patients) causes clopidogrel resistance. METHODS: From deidentified database of all medical records, patients were selected with ICD-9/10 code for ICAD, availability of CYP2C19 genotype, clopidogrel exposure, and established patient care. Dual-antiplatelet therapy patients were included. Patients with intracranial angioplasty/stenting, other primary neurovascular condition, prior ischemic stroke, or observation time <1 month were excluded. Time-to-event analysis using Cox regression was conducted to model first-time ischemic stroke events based on CYP2C19 loss-of-function allele and adjusted for age, gender, race, length of aspirin, length of concurrent antiplatelet/anticoagulant treatment, diabetes, coagulopathy, hypertension, heart disease, atrial fibrillation, and lipid disorder. RESULTS: A total of 340 patients were included (median age 68, 58% male, 88% Caucasian, 26% CYP2C19 loss-of-function). A total of 37 patients (10.9%) suffered a first-time ischemic stroke during observation period. Median observation time was 2.82 [IQR 1.13-5.25] years. Median length of concurrent aspirin use was 99% [96-100] of observation period. CYP2C19 loss-of-function allele was associated with ischemic stroke event (HR 2.2, 95% CI 1.1-4.3, P = . 020) after adjustment. CONCLUSION: CYP2C19 loss-of-function is associated with 2.2-fold increased risk of first-time ischemic stroke for ICAD patients during clopidogrel exposure. This genetic risk may have interacted with results of previous clinical trials, making it difficult to clearly interpret differences between medical and procedural management. These results may indicate a need for increased CYP2C19 testing to inform patient-specific selection of antiplatelet agent for ICAD. For ICAD patients with already-established CYP2C19 loss-of-function, clinicians should consider antiplatelet alternatives to clopidogrel for primary stroke prevention.